Mismatch Negativity Responses in Schizophrenia: A Combined fMRI and Whole-Head MEG Study. - Kircher, Tilo T. J.; Rapp, Alexander; Grodd, Wolfgang (American Journal of Psychiatry, 2004)
Objective: Mismatch negativity is an event-related brain response sensitive to deviations within a sequence of repetitive auditory stimuli. It is thought to reflect short-term sensory memory and is independent of higher-level cognitive processes. Mismatch negativity response is diminished in patients with schizophrenia. Little is known about the mechanisms of this decreased response, the contribution of the different hemispheres, and its locus of generation. Method: Patients with schizophrenia (N=12) and matched comparison subjects (N=12) were studied. A novel design to measure mismatch negativity responses to deviant auditory stimuli was generated by using the switching noises from the functional magnetic resonance imaging (fMRI) scanner, thus avoiding any interfering background sound. Stimuli included deviants of amplitude (9 dB lower) and duration (76 msec shorter) presented in a random sequence. The scanner noise was recorded and applied to the same subjects in a whole-head magnetoencephalography (MEG) device. Neuromagnetic and hemodynamic responses to the identical stimuli were compared between the patients and comparison subjects. Results: As expected, neuromagnetic mismatch fields were smaller in the patient group. More specifically, a lateralization to the right for duration deviance was only found in comparison subjects. For the relative amplitude of the blood-oxygen-level-dependent signal (measured with fMRI), differences emerged in the secondary (planum temporale), but not primary (Heschl's gyrus), auditory cortex. Duration deviants achieved a right hemispheric advantage only in the comparison group. A significantly stronger lateralization to the left was found for the deviant amplitude stimuli in the patients. Conclusions: The data support the view of altered hemispheric interactions in the formation of the short-term memory traces necessary for the integration of auditory stimuli. This process is predominantly mediated by the planum temporale (secondary auditory cortex). Altered interaction of regions within the superior temporal plane and across hemispheres could be in part responsible for language-mediated cognitive (e.g., verbal memory) and psychopathological (hallucinations, formal thought disorder) symptoms in schizophrenia. Reprinted by permission of the publisher.